The Role of Novelty-Seeking Traits in Contemporary Knowledge Creation - Erkan Gören (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper hypothesizes and empirically establishes the persistent effects of novelty-seeking traits on cross-country differences in scientific knowledge creation. I use data on the prevalence of specific allele variants of the human DRD4 exon III gene, which population geneticists have linked to the human phenotype of novelty-seeking behavior to examine its relationship to scientific knowledge creation in society. The results suggest a positive and statistically significant linear relationship between both outcomes that is consistent with the hypothesis that the prevalence of novelty-seeking traits in society facilitates scientific knowledge creation through beneficial human behaviors related to risk-taking and explorative behavior. The empirical findings remain qualitatively unaffected when controlling for additional historical, biogeographical, and socioeconomic factors that appear as additional important determinants in the creation of scientific knowledge in society.
Keywords: N70; O30; O50; Z10; N70; O30; O50; Z10; 330; DRD4 Exon III; Novelty-Seeking Traits; Entrepreneurial Activity; Knowledge Creation; Technological Progress; Economic Development; Natural Selection; Genetic Diversity